Methylprednisolone or dexamethasone, which one is superior corticosteroid in the treatment of hospitalized COVID-19 patients: a triple-blinded randomized controlled trial - Ranjbar, Keivan; Moghadami, Mohsen; Mirahmadizadeh, Alireza; Fallahi, Mohammad Javad; Khaloo, Vahid; Shahriarirad, Reza; Erfani, Amirhossein; Khodamoradi, Zohre; Gholampoor Saadi, Mohammad Hasan (BMC infectious diseases, 2021)
Although almost a year has passed since the Coronavirus disease 2019 (COVID-19) outbreak and promising reports of vaccines have been presented, we still have a long way until these measures are available for all. Furthermore, the most appropriate corticosteroid and dose in the treatment of COVID-19 have remained uncertain. We conducted a study to assess the effectiveness of methylprednisolone treatment versus dexamethasone for hospitalized COVID-19 patients. In this prospective triple-blinded randomized controlled trial, we enrolled 86 hospitalized COVID-19 patients from August to November 2020, in Shiraz, Iran. The patients were randomly allocated into two groups to receive either methylprednisolone (2 mg/kg/day; intervention group) or dexamethasone (6 mg/day; control group). Data were assessed based on a 9-point WHO ordinal scale extending from uninfected (point 0) to death (point 8). There were no significant differences between the groups on admission. However, the intervention group demonstrated significantly better clinical status compared to the control group at day 5 (4.02 vs. 5.21, p = 0.002) and day 10 (2.90 vs. 4.71, p = 0.001) of admission. There was also a significant difference in the overall mean score between the intervention group and the control group, (3.909 vs. 4.873 respectively, p = 0.004). The mean length of hospital stay was 7.43 ± 3.64 and 10.52 ± 5.47 days in the intervention and control groups, respectively (p = 0.015). The need for a ventilator was significantly lower in the intervention group than in the control group (18.2% vs 38.1% p = 0.040). In hospitalized hypoxic COVID-19 patients, methylprednisolone demonstrated better results compared to dexamethasone. The trial was registered with IRCT.IR (08/04/2020-No. IRCT20200204046369N1 ).